EKSPLORASI NILAI-NILAI KARAKTER DALAM KUNUN KERINCI - Suci Maiza (EDU RESEARCH, 2024)
This study aims to determine the structure, function, and environmental storytelling in folklore Kunun. This research aims to explore the values of character education contained in the Kunun Kerinci through the structure, function, and environmental storytelling in folklore Kunun. The method used descriptive method, the form of qualitative and structural approach. The data in this research are Kunun texts which are spread orally as well as references related to Kunun. Data in the form of oral texts that were collected were then analyzed through the stages of transcription, transliteration and translation which were then classified based on the problem formulation, namely structure, storytelling environment and social function. The theme raised in Kunun Kerinci is the social theme of family and community relations. The environment of Kunun storytelling includes the elements that tell the story or that bring it, the opportunity to carry it out, the purpose and relationship of the story with the surrounding environment. Kunun is spread across the Kerinci area, which contains character values ​​that can be used to support learning in schools, including being honest, doing good, being responsible, helping others, respecting parents and being disciplined.